3D-printing analysis of surface finish. (2021) - Morampudi, Priyadarsini; Ramana, V.S.N. Venkata; Prabha, K. Aruna; Swetha, S.; Rao, A.N. Brahmeswara
Abstract: 3D printing is a process of producing 3D objects from CAD model. Using additive processes, 3D printing is done where a part is formed layer by layer. A melted affidavit model conveying ordinary surface examples with various element sizes and angle proportions will be produced on a FDM framework with various form directions. The surface finish of each 3D printed part will be inspected. The objective is to evaluate surface finish of different parts by changing the layer thickness and other parameters such as infill, infill pattern, roof thickness, floor thickness, and number of shells were considered for the study of build time optimization and also find out the relation between surface roughness and layer thickness.